The influence of concrete mix composition and environmental exposure on long-term chloride ingress in concrete - Heiyantuduwa-Beushausen, Rukshani Heiyantuduwa (Department of Civil Engineering, 2023)
The parameters influencing long-term chloride ingress in concrete structures exposed to different environmental conditions in South Africa were investigated, aiming at improving service life prediction models for reinforced concrete structures situated in marine exposure classes. Time-dependent chloride ingress was measured over a period of roughly 4 years with respect to the influences of binder type, w/b ratio and environmental conditions, exposing samples to submerged, tidal, splash/spray and airborne chloride exposure in the Atlantic Ocean in Cape Town and the Indian Ocean in Durban. As a comparison, chloride ingress was measured under laboratory-controlled conditions. The data was analysed to identify the parameters used in the modelling of long-term chloride ingress into concrete using Fick's laws of diffusion. The time dependency of apparent diffusion coefficients and chloride surface concentrations was identified and used in the long-term service life prediction with respect to the various experimental parameters. Based on the model predictions, the combined influences of binder type, w/b ratio, exposure condition and cover depth on the expected service life duration of RC structures in South African marine environments were investigated quantitively.